The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/nmicrobiol.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Clostridium difficile toxin A

Abstract: Clostridium difficile infection is the leading cause of hospital-acquired diarrhoea and pseudomembranous colitis. Disease is mediated by the actions of two toxins, TcdA and TcdB, which cause the diarrhoea, as well as inflammation and necrosis within the colon1,2. The toxins are large (308 and 270 kDa, respectively), homologous (47% amino acid identity) glucosyltransferases that target small GTPases within the host3,4. The multidomain toxins enter cells by receptor-mediated endocytosis and, upon exposure to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
115
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 46 publications
11
115
1
Order By: Relevance
“…A number of C. difficile virulence factors have a Zn requirement; however, the impact of Zn on CDI has yet to be explored 1417 . To test this, we used a mouse model of CDI that induces susceptibility to C. difficile through administration of cefoperazone (0.5 mg/ml)(Supplementary Fig.…”
mentioning
confidence: 99%
“…A number of C. difficile virulence factors have a Zn requirement; however, the impact of Zn on CDI has yet to be explored 1417 . To test this, we used a mouse model of CDI that induces susceptibility to C. difficile through administration of cefoperazone (0.5 mg/ml)(Supplementary Fig.…”
mentioning
confidence: 99%
“…3B). We presume that the residual activity of the mutant seen in the caspase-3/7 activation assay is a result of residual glucosylating activity, the effects of which are detectable only at the highest concentration tested (34,44). When the cells were challenged with higher concentrations (Ն100 pM) of TcdB, very little caspase activation was detected (Fig.…”
Section: Figmentioning
confidence: 93%
“…TcdA and TcdB have four functional domains 100,106 : an amino-terminal glucosyltransferase domain (GTD), an autoprotease domain (APD), a pore-forming and delivery domain, and the combined repetitive oligopeptides (CROPS) domain, which extends from around residue 1,830 to the carboxyl terminus (FIG. 5a,b).…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…5a,b). A combination of electron microscopy and X-ray crystallography studies has revealed the structural organization of these domains in TcdA and suggests that the structure of TcdB is similar 106,107 . TcdA and TcdB enter cells via receptor-mediated endocytosis 108 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%